2010
DOI: 10.1111/j.1751-2980.2010.00444.x
|View full text |Cite
|
Sign up to set email alerts
|

Addition of gentamicin to endoscopic retrograde cholangiopancreatography (ERCP) contrast medium towards reducing the frequency of septic complications of ERCP

Abstract: These results support the use of gentamicin in the contrast medium injected into the biliary system as an ancillary method to prevent post-ERCP sepsis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 46 publications
1
4
0
Order By: Relevance
“…In vitro studies have proven that aminoglycosides retain their antibacterial properties when mixed to ERC contrast media. Thus, the aminoglycosides tobramycin and gentamicin efficiently eliminated common biliary bacteria such as E. coli , Klebsiella pneumonia , Proteus vulgaris and Pseudomonas aeruginosa [21, 27]. In line with these findings, we observed a significantly reduced post-ERC infection rate in patients with biliary obstruction when antimicrobial agents were added into the ERC media.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…In vitro studies have proven that aminoglycosides retain their antibacterial properties when mixed to ERC contrast media. Thus, the aminoglycosides tobramycin and gentamicin efficiently eliminated common biliary bacteria such as E. coli , Klebsiella pneumonia , Proteus vulgaris and Pseudomonas aeruginosa [21, 27]. In line with these findings, we observed a significantly reduced post-ERC infection rate in patients with biliary obstruction when antimicrobial agents were added into the ERC media.…”
Section: Discussionsupporting
confidence: 71%
“…This concerns particularly patients with hilar strictures and PSC [19]. Patients with post-transplant biliary strictures undergoing ERC represent other feasible candidates for systemic antibiotic prophylaxis [21]. Since systemically administered antibiotics poorly penetrate into the bile in case of biliary obstruction [20, 25, 26], a theoretical benefit of injecting antimicrobial agents directly into the bile tracts during ERC is assumable.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several previous studies showed that patients with obstructed bile ducts are at highest risk of developing septic complications following ERCP, especially when the drainage was not complete 3,10,11. And poorly disinfected duodenoscopy was considered as a risk factor of post-ERCP bacteremia especially in Pseudomonas aeruginosa infection 12.…”
Section: Introductionmentioning
confidence: 99%
“…In a study done in Texas, Gentamycin incorporated into the contrast material was successful in reducing the rates of post-ERCP bacteremia. [10] In another study, antibiotics were used parenterally prior to ERCP but failed to produce any significant change in the incidence of bacteremia. [11]…”
Section: Discussionmentioning
confidence: 99%